2021
DOI: 10.3389/fpls.2021.703712
|View full text |Cite
|
Sign up to set email alerts
|

The Algal Polysaccharide Ulvan Induces Resistance in Wheat Against Zymoseptoria tritici Without Major Alteration of Leaf Metabolome

Abstract: This study aimed to examine the ability of ulvan, a water-soluble polysaccharide from the green seaweed Ulva fasciata, to provide protection and induce resistance in wheat against the hemibiotrophic fungus Zymoseptoria tritici. Matrix-assisted laser desorption/ionization-time-of-flight-mass spectrometry (MALDI-TOF-MS) analysis indicated that ulvan is mainly composed of unsaturated monosaccharides (rhamnose, rhamnose-3-sulfate, and xylose) and numerous uronic acid residues. In the greenhouse, foliar application… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 41 publications
0
6
1
Order By: Relevance
“…This conclusion contradicts the widely reported beneficial effects of Ulva extracts on plant growth and health (e.g. Kidgell et al 2019) and two specific studies reporting disease reductions and unaltered metabolomes after application of Ulva extracts to Triticum aestivum (de Borba et al 2021) and Medicago truncatula (Cluzet et al 2004). However, the inconsistent nature of our results in relation to disease protection are not unique (Abouraicha et al 2015;de Borba et al 2019;Delgado et al 2013).…”
Section: Discussioncontrasting
confidence: 61%
“…This conclusion contradicts the widely reported beneficial effects of Ulva extracts on plant growth and health (e.g. Kidgell et al 2019) and two specific studies reporting disease reductions and unaltered metabolomes after application of Ulva extracts to Triticum aestivum (de Borba et al 2021) and Medicago truncatula (Cluzet et al 2004). However, the inconsistent nature of our results in relation to disease protection are not unique (Abouraicha et al 2015;de Borba et al 2019;Delgado et al 2013).…”
Section: Discussioncontrasting
confidence: 61%
“…Currently, it has been reported that it has antimicrobial activity against a variety of pathogenic microorganisms, and some researchers have found that magnolol achieves an antimicrobial effect by destroying plasma membranes (Sun et al, 2015a;Chen et al, 2019). In addition, the film-forming substances are polysaccharide compounds, which can induce plant disease resistance and may have a synergistic effect with magnolol (Borba et al, 2021;Dong et al, 2023). Field experiments proved that the Mag@CMCS@CPSG film had a good controlling effect on rice sheath blight disease.…”
Section: Discussionmentioning
confidence: 99%
“…Oryzae , Xanthomonas oryzae pv. Oryzicola Spray, Add to the bacterial solution Disrupt cell membranes, induce PAL, POX and PPO activity, callose deposition, increase synthesis of polyphenols and abscisic acid content Cellodextrins [45] Plant Grapevine Gray mold Botrytis cinerea Add elicitor to cell culture Induce defense-related genes, induction of oxidative burst and cytosolic calcium variation, phytoalexin accumulation Algino-oligosaccharides [46] , [47] Seaweed Soybean, Rice Rice blast Pseudomonas aeruginosa , Magnaporthe grisea Spray Induce PAL, POD, CAT activity, accumulation of phytoalexin Sulfated fucan oligosaccharides [48] Seaweed Tobacco Tobacco mosaic disease Tobacco mosaic virus Add elicitor to cell culture Induce PAL activity, PR genes, accumulation of phytoalexin and SA, release of H 2 O 2 Ulvans [49] , [50] Macroalgae Medicago truncatula, Common bean, Grapevine, Cucumber, Wheat Bean rust, Angular leaf spot, Septoria tritici blotch Colletotrichum trifolii , Erysiphe polygoni , Erysiphe necator , Sphareotheca fuliginea , Uromyces appendiculatus , Pseudocercospora griseola , Zymoseptoria tritici Spray Induce defense-related genes, ROS metabolism and octadecanoids Carrageenans [51] Rodophyta Tobacco Tobacco mosaic disease Tobacco mosaic virus, Botrytis cinerea, Pectobacterium carotovorum Spray Induce OXO, PAL activity, jasmonic acid related genes and the accumulation of several phenylpropanoid compounds
Fig. 5 Chemical structures of oligosaccharides with immune inducer activities.
…”
Section: Oligosaccharides (Ogas)mentioning
confidence: 99%